Potential of the microalgae chlorella sorokiniana for carbon capture from winery fermentations and wastewater bioremediation - McMurtry, Sarah K. (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.